Association Between Perceived Stress and Prenatal Depressive Symptoms: Moderating Effect of Social Support - Li P (Dove Medical Press, 2021)
Pengsheng Li,1,2,* Haiyan Wang,2,3,* Jinping Feng,2 Gengdong Chen,1,2 Zixing Zhou,1,2 Xiaoyan Gou,2,3 Shaoxin Ye,1,2 Dazhi Fan,1,2 Zhengping Liu,1,2 Xiaoling Guo2 1Foshan Fetal Medicine Research Institute, Affiliated Foshan Maternity & Child Healthcare Hospital, Southern Medical University, Foshan, People’s Republic of China; 2Department of Obstetrics, Affiliated Foshan Maternity & Child Healthcare Hospital, Southern Medical University, Foshan, People’s Republic of China; 3Biobank, Foshan Fetal Medicine Research Institute, Affiliated Foshan Maternity & Child Healthcare Hospital, Southern Medical University, Foshan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaoling GuoDepartment of Obstetrics, Affiliated Foshan Maternity & Child Healthcare Hospital, Southern Medical University Email fsguoxl@163.comPurpose: Prenatal depressive symptoms are an important mental health problem during pregnancy. We aimed to explore the moderating role of social support on the association between perceived stress and prenatal depressive symptoms.Materials and Methods: A cross-sectional study was conducted at an obstetrics clinic. A total of 1846 women completed a self-administered questionnaire, with a response rate of 91.8%.Results: Of the 1846 participants, 28.2% reported prenatal depressive symptoms (Edinburgh postnatal depression scale score ≥ 9). After adjusting for demographic characteristics, gestational age, exercise, and passive smoking, both perceived stress (adjusted odds ratio (AOR): 1.210, 95% confidence interval (CI): 1.178– 1.242) and social support (AOR: 0.950, 95% CI: 0.932– 0.968) were associated with prenatal depressive symptoms. Moreover, social support had a moderating effect on the association between perceived stress and prenatal depressive symptoms (p < 0.001), and pregnant women with low social support were more likely to be affected by stress and experience prenatal depressive symptoms.Conclusion: Our study suggests that higher social support reduces the impact of stress on pregnant women, which in turn, decreases the risk of prenatal depressive symptoms. Therefore, interventions aimed at improving social support should be considered for the prevention and treatment of prenatal depressive symptoms.Keywords: prenatal depressive symptoms, stress, social support, moderation